Sleep, sedentary behavior and physical activity: changes on children’s routine during the COVID-19 - Luís Carlos Barbosa Silva; Cinthya Rafaella Magalhães da Nóbrega Novaes; Ronaldo Alexandre de Lima Júnior; Bruno Barbosa Giudicelli; Arnaldo Tenório da Cunha Júnior; Maria Cecília Marinho Tenório; Clarice Maria de Lucena Martins; Rafael Miranda Tassitano (Revista Brasileira de Atividade Física e Saúde)
Social isolation was adopted as a strategy to reduce the transmission speed of the severe acute respiratory syndrome of coronavirus 2 (SARS-CoV-2) in several countries in the world, including Brazil. As a result, schools were closed and the routines of children altered, affecting sleep, sedentary behavior, and physical activity. The present study aims to compare the children’s weekly routine and time spent on sleep, sedentary behavior and physical activity before and during the Coronavirus disease 2019 (COVID-19) pandemic. A cross-sectional study with a quantitative and qualitative approach was performed, with 120 parents, mothers or guardians of children from 5 to 10 years of age of both sexes enrolled in 5 full-time schools in Arapiraca, Alagoas, Brazil. To meet the research objective, two interviews were conducted between 27 May and 5 June, out addressing aspects of sleep, sedentary behavior, and physical activity before and during the COVID-19 pandemic. In the analysis of quantitative data, the paired sample t test was performed, while for qualitative data, discourse analysis was used. Significant differences (p < 0.05) were found in the routine and in sleep time (increase 10%) and screen time (increase 36%) before vs during the COVID-19 pandemic, on weekdays and weekends. There was also a reduction in the practice of physical activity (54%). Therefore, the findings indicate that behaviors during the COVID-19 pandemic could be harmful to children’s health and that the school may be an important social environment to protect children from exposure to these behaviors.